A bifunctional catalyst for coupling water-gas shift and plastic hydrogenolysis reactions, and methods of making and using the same
Patent Information
- Application Number
- CN202610414086.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-31
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-03-31
AI Technical Summary
[0009]针对现有技术中废弃塑料化学回收依赖外部供氢、反应条件苛刻、工艺成本高等问题,本发明的目的是提供一种新型双功能催化剂,该催化剂能在较低温度下,高效耦合水煤气变换反应与塑料氢解反应,利用一氧化碳(CO)和水(H2O)作为原位氢源,将废弃塑料选择性转化为高价值液体燃料和化学品
1,本发明提供了一种用于耦合水煤气变换与塑料氢解反应的双功能催化剂及其制备方法,该催化剂在较低温度下即能高效催化水煤气变换反应,产生高活性的原位氢;该原位氢可即时用于聚丙烯塑料分子链的精准切断与结构重整,实现将废弃聚丙烯塑料定向转化为高价值液体燃料。实现了水煤气变换产氢与塑料氢解过程的高效耦合,为废弃塑料和工业废气的协同高值化利用提供创新的解决方案。
Smart Images

Figure CN122032580B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst preparation and waste resource utilization technology, specifically relating to a bifunctional catalyst for coupling water-gas shift and plastic hydrogenolysis reactions, its preparation method and application. Background Technology
[0002] The statements herein provide only background information in relation to this invention and do not necessarily constitute prior art.
[0003] The widespread use of plastics, especially polyolefin plastics, has brought about a significant environmental challenge: "white pollution." Currently, the main methods for the disposal and resource recovery of waste plastics include: mechanical recycling based on multiple melt-regeneration processes; recovering heat energy through incineration of waste plastics; and chemical recycling, which decomposes plastic polymers into monomers or small-molecule chemicals. Existing chemical recycling technologies mainly include: (1) Pyrolysis: High-temperature pyrolysis under anaerobic or hypoxic conditions, resulting in complex products (coexistence of gas, liquid and waxy substances), poor selectivity, high cost of subsequent separation and purification, and huge energy consumption.
[0004] (2) Catalytic cracking / hydrocracking: Introducing a catalyst can lower the reaction temperature and improve product selectivity. However, most existing technologies rely on external hydrogen supply (such as high-pressure hydrogen), which poses risks to storage and transportation safety and high costs, thus restricting their large-scale application. How to achieve a low-cost hydrogen source supply under mild conditions is a bottleneck currently facing plastic catalytic conversion technology.
[0005] In his master's thesis on the production of hydrogen-rich gas from plastic pyrolysis-catalytic reforming based on nickel-iron catalysts, Han Shaojie studied the achievement of high syngas yield at 850℃ using iron oxide, nickel ferrite, and NiFe / MA 20 as catalysts in a feed mass ratio of 1:10. However, the high reaction temperature hinders cost reduction.
[0006] The water-gas shift reaction (CO + H₂O → CO₂ + H₂) is a crucial process for large-scale industrial hydrogen production. The water-gas shift reaction requires a catalyst to proceed. The most widely used catalyst in industry is iron-chromium oxide (FeCrO₂). While FeCrO₂ catalysts exhibit high catalytic activity at high temperatures, promoting rapid reaction, the metal components are prone to sintering and agglomeration at high temperatures. This leads to larger active component particles, reducing the contact area between the active component and the reactants. Consequently, the catalyst's ability to reform intermediate products decreases, resulting in reduced catalyst activity and limiting product conversion rates.
[0007] If the water-gas shift reaction and the plastic hydrogenolysis reaction can be efficiently coupled in the same catalytic system, using inexpensive CO and H2O as hydrogen sources, and generating highly active hydrogen on-site for immediate use in plastic chain breaking, it is expected to fundamentally break the dependence on external hydrogen sources and achieve process intensification and economy.
[0008] However, developing a bifunctional catalyst that simultaneously exhibits excellent water-gas shift (WGS) activity and plastic C-bond hydrogenolysis activity at lower temperatures is the core challenge and difficulty in realizing this technological concept. Summary of the Invention
[0009] To address the problems of existing technologies in the chemical recycling of waste plastics, such as reliance on external hydrogen supply, harsh reaction conditions, and high process costs, the purpose of this invention is to provide a novel bifunctional catalyst that can efficiently couple the water-gas shift reaction and the plastic hydrogenolysis reaction at a lower temperature. It utilizes carbon monoxide (CO) and water (H2O) as in-situ hydrogen sources to selectively convert waste plastics into high-value liquid fuels and chemicals.
[0010] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a bifunctional catalyst for coupling water-gas shift and plastic hydrogenolysis reactions, comprising a porous support and a composite active component supported thereon, wherein the surface of the porous support has acidic sites, the acidic sites being Brønsted acid sites or Lewis acid sites; the composite active component comprises Fe3O4 nanoparticles, wherein the exposed crystal faces of the Fe3O4 nanoparticles are dominated by {311}. And a co-catalyst metal M, wherein the co-catalyst metal M is selected from at least one of the transition metals Co, Ni, Mo, and W or the noble metals Ru, Pd, and Pt.
[0011] In this invention, the d-electron cloud of metal nanoparticles is used to efficiently regulate the desorption and addition of hydrogen. Transition metals (such as Fe, Ni, Co, Cu, etc.) commonly possess unsaturated d orbitals, meaning their d-electron layers are not fully filled, containing empty orbitals or easily excited electrons. After processing, non-transition metals can, to some extent, mimic the behavior of transition metals and undergo addition reactions with hydrogen like transition metals.
[0012] In the bifunctional catalyst provided by this invention, the porous support is used to provide a high specific surface area and suitable pore structure to promote the dispersion of active components and the mass transfer of reactants. The {311} crystal facet of iron(III) oxide has higher surface energy and a higher density of unsaturated coordination atoms, resulting in a more "rough" atomic arrangement and numerous steps and kinks. These sites are more ideal for the adsorption and activation of H2O and CO. Experiments have shown that Fe3O4 nanoparticles predominantly expose the {311} crystal facet, which is beneficial for improving the selectivity of liquid fuels.
[0013] In some embodiments of the present invention, the porous support is selected from one or more composite materials of biomass-derived porous carbon, molecular sieves, metal oxides, and metal carbides; wherein, the molecular sieve is selected from one or more composite materials of Y-type molecular sieves, Beta molecular sieves, and ZSM-5 molecular sieves; the metal oxide is selected from one or more composite materials of alumina, silicon oxide, and zinc oxide; and the metal carbide is selected from one or two composite materials of silicon carbide and molybdenum carbide. Biomass-derived porous carbon, molecular sieves, and metal oxides have high specific surface area and pore structure, and are common porous supports; in recent years, researchers have prepared porous silicon carbide and molybdenum carbide using template methods, sintering methods, and pore-forming agent methods for use as porous supports.
[0014] In some embodiments of the present invention, the Fe3O4 nanoparticles form an M-Fe3O4 composite active phase that interacts closely with the co-catalytic metal M, and the nanoparticles supported on the support have a particle size of 5-50 nm. The molar ratio of the co-catalytic metal M to Fe3O4 is (0.25-1):1.
[0015] Preferably, the carrier is biomass-derived porous carbon with a specific surface area of 500-1000 m². 2 / g, with a pore size of 5-15 nm.
[0016] Secondly, the present invention provides a method for preparing a bifunctional catalyst for coupling water-gas shift and plastic hydrogenolysis reactions, comprising the following steps: S1. Support preparation: Prepare or provide a porous support; S2. In-situ synthesis and loading of Fe3O4 nanoparticles: Fe3O4 nanoparticles with exposed {311} crystal planes were grown in situ on the support using a hydrothermal method synergistically controlled by polymer and surfactant to obtain Fe3O4@support precursor; S3. Loading of co-catalytic metal M: The salt solution containing co-catalytic metal M is loaded onto the Fe3O4@support precursor obtained in step S2 by impregnation method; S4. Activation treatment: The loaded material is heat-treated in a protective or reducing atmosphere to obtain the bifunctional catalyst.
[0017] In step S1, when the carrier is biomass-derived porous carbon, its preparation method includes: After crushing and drying the biomass raw material, it is mixed with an aqueous solution of phosphoric acid and impregnated at 60-90°C for 2-6 hours. Then, the impregnated mixture is heated to 400-600°C at a rate of 5-15°C / min under an inert atmosphere and held at that temperature for 1-3 hours for pyrolysis activation. After cooling, the obtained carbon material is washed with hot water until neutral and dried. Subsequently, the dried carbon material is heat-treated in air or an inert atmosphere at 300-400°C for 0.5-2 hours. Finally, the heat-treated carbon material is stirred with concentrated sulfuric acid at 60-150°C for 1-3 hours, washed, and dried to obtain the biomass porous carbon material.
[0018] Preferably, in step S2, the polymer is selected from one or more of polyvinylpyrrolidone, polyvinyl alcohol, and polyethylene glycol; Preferably, in step S2, the surfactant is selected from one or more of citrate, tartrate, oxalate, EDTA and its derivatives.
[0019] Preferably, in step S2, the polymer is polyvinylpyrrolidone (PVP) and the surfactant is sodium citrate.
[0020] Surfactants contain multiple carboxylate groups that react with Fe. 3+ / Fe 2+ It exhibits extremely strong coordination ability. Citrate ions preferentially and strongly adsorb onto low-index crystal faces such as {111} and {100} of Fe3O4 because the arrangement of Fe atoms on these faces is more conducive to its polydentate coordination. This adsorption prevents the deposition and reduction of iron precursor species (such as Fe-OH) on these crystal faces, kinetically slowing down the growth rate of these crystal faces. In contrast, high-index crystal faces such as {311} exhibit weaker adsorption of citrate ions, thus the {311} crystal face dominates. The long-chain molecules of the polymer PVP can adsorb onto the surface of the generated Fe3O4 nanoparticles, preventing Ostwald ripening and aggregation of the nanoparticles in the high-temperature and high-pressure hydrothermal environment through their steric hindrance effect. This helps to obtain nanoparticles with uniform size and good dispersibility.
[0021] Preferably, the hydrothermal method specifically involves dissolving iron salt, surfactant, and polymer in water, adding a carrier, adjusting the pH to 12-13, then transferring the mixture to a hydrothermal reactor and reacting it at 150-180°C for 10-14 hours. After the reaction is complete, the mixture is washed and dried to obtain the Fe3O4@carrier precursor.
[0022] Further, in step S4, the activation treatment preferably includes two heat treatments: first, calcination at 300-500°C for 1-5 hours in an oxygen-containing atmosphere (such as air); then, reduction at 350-500°C for 1-4 hours in a reducing atmosphere (such as a H2 / Ar or H2 / N2 mixture). During the activation treatment, calcination is first carried out in an air atmosphere to oxidize the metal salt into easily reducible metal oxides, such as nickel nitrate being converted into nickel oxide and ferric nitrate being converted into ferric oxide. Then, reduction is performed to reduce the metal oxides to metal and magnetite (ferric oxide is reduced to magnetite at 400-500°C, while the reduction temperature of magnetite is above 500°C, and the reduction temperature of nickel is around 400°C).
[0023] Thirdly, the present invention provides the application of the bifunctional catalyst described in the first aspect for coupling water-gas shift and plastic hydrogenolysis reaction in the resource utilization of waste plastics.
[0024] The specific method of the application is as follows: waste plastic, water, the bifunctional catalyst described in the first aspect, and carbon monoxide are placed together in a reactor. Under the reaction conditions, the catalyst simultaneously catalyzes the water-gas shift reaction to generate active hydrogen, and uses this active hydrogen to catalyze the hydrogenolysis reaction of the plastic, converting it into liquid fuel. Under the reaction conditions, the catalyst simultaneously performs two functions: (1) catalyzing the water-gas shift reaction: CO + H2O → CO2 + H2, generating highly active in-situ hydrogen; (2) catalyzing the hydrogenolysis reaction: using the generated in-situ hydrogen to selectively break the C-C bonds in the plastic macromolecules, converting the plastic into liquid fuel and chemicals.
[0025] Furthermore, the waste plastic is polypropylene, polyethylene, or polyvinyl chloride, etc. The reaction conditions include one or more of the following: (1) The mass ratio of waste plastic to catalyst is 10:1 to 100:1; (2) The partial pressure of carbon monoxide in the reaction system is 3-8 MPa; (3) The mass ratio of waste plastic to water is 3:1 to 20:1; (4) The reaction temperature is 300-400℃; (5) The reaction time is 2 to 15 hours.
[0026] Regarding the support structure, the bifunctional catalyst provided by this invention features innovative structural design and multifunctionality: Through pore engineering and activation treatment, this invention successfully prepared a high specific surface area porous carbon support using biomass as a precursor. This support possesses excellent physical structure, with a specific surface area as high as 500-1000 m². 2With a pore size concentrated in the mesoporous range of 5-10 nm, the aluminosilicate molecular sieve provides ample space for highly dispersed loading of active components and greatly optimizes the mass transfer efficiency between reactants and products. Furthermore, its surface possesses abundant acidic sites; through acid treatment and sulfonation, abundant Brønsted acid (B acid) sites are introduced onto the support surface. In aluminosilicate molecular sieves, the cation with the balanced charge is a proton, inherently possessing Brønsted acidity (B acid). These acidic sites not only enhance the catalyst's adsorption and activation ability for plastic molecules such as polypropylene, but more importantly, they can induce the formation of highly active carbocation intermediates in plastic macromolecules, thereby effectively reducing the activation energy for C / C bond breaking and laying a crucial foundation for subsequent directional conversion. Its regular pore structure allows for physical shape selection of product molecules, contributing to improved selectivity for target liquid fuels.
[0027] Regarding the catalytic mechanism, the bifunctional catalyst prepared in this invention represents a breakthrough in multi-active-site synergistic catalysis: the MX-(Fe3O4)Y@BC catalyst (X to Y ratio of 0.25-1:1) prepared in this invention is not a simple physical mixture of active components, but rather a synergistic catalytic system with strong electronic interactions, composed of metal nanoparticles (M), Fe3O4, and an acidic support. In this catalyst, the metal nanoparticles are mainly responsible for the in-situ generation of hydrogen and the saturation of intermediates formed after the bond breaking of polypropylene (PP), thus forming a stable product. XPS analysis reveals electron transfer in Fe3O4. In the experimental samples, a comparison between Fe3O4 / USY and Ni-Fe3O4 / USY shows that the introduction of Ni into the catalyst significantly alters the 2p valence state distribution of Fe, with a significant increase in the number of divalent Fe states and a decrease in the number of trivalent Fe states, demonstrating electron storage and migration.
[0028] The superiority of its catalytic mechanism is reflected in the following aspects: First, it is a relay catalysis of "CC bond activation-hydrogen transfer-saturation". The acidic support (BC) is responsible for activating plastic molecules to generate carbocations and initiating the breaking of CC bonds (β-breakage); the metal nanoparticles (M) efficiently regulate hydrogen desorption and hydrogenation through their d electron clouds, hydrogenating and saturating the unstable intermediate into a stable product, and effectively inhibiting the carbon deposition side reaction caused by deep dehydrogenation. Second, the efficient electron transfer and energy coupling of Fe3O4 nanoparticles, due to their Fe... 2+ / Fe 3+ Its mixed valence state characteristics enable excellent electron migration and storage capabilities. It may act as a "bridge" for electron transfer within the system, optimizing electronic synergy between the metal M and the acidic support BC, thereby improving the efficiency of the entire catalytic cycle. Finally, through precise integration of structure and function, highly dispersed M-Fe3O4 composite nanoparticles (5-50 nm in diameter) provide abundant active interfaces; the introduction of the Fe3O4 component also endows the catalyst with magnetism, facilitating rapid separation and recycling after the reaction.
[0029] The beneficial effects achieved by one or more embodiments of the present invention described above are as follows: 1. This invention provides a bifunctional catalyst for coupling water-gas shift reaction and plastic hydrogenolysis, and its preparation method. This catalyst can efficiently catalyze the water-gas shift reaction at relatively low temperatures, producing highly active in-situ hydrogen. This in-situ hydrogen can be used immediately for the precise cleavage and structural restructuring of polypropylene plastic molecular chains, enabling the directional conversion of waste polypropylene plastic into high-value liquid fuel. This achieves efficient coupling of hydrogen production from water-gas shift reaction and the plastic hydrogenolysis process, providing an innovative solution for the synergistic high-value utilization of waste plastics and industrial waste gas.
[0030] 2. The bifunctional catalyst provided by the present invention has excellent catalytic performance: it can achieve the complete conversion of waste plastics such as polypropylene under relatively mild conditions, overcoming the disadvantages of traditional pyrolysis or hydrogenation processes that require high temperature and high pressure, and significantly reducing energy consumption.
[0031] 3. This application provides the aforementioned bifunctional catalyst and its application in the resource utilization of waste plastics. This technology ingeniously utilizes the water-gas shift reaction, using CO and H2O as in-situ hydrogen sources, replacing expensive and dangerous external high-pressure hydrogen, and realizing the green process integration of "treating waste (waste plastics) with waste (waste gas)," which has significant environmental benefits and cost advantages; it provides an integrated solution for plastic pollution control and carbon resource recycling, and shows significant technical and economic value in practical applications. Attached Figure Description
[0032] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0033] Figure 1 The nitrogen adsorption-desorption curves of the catalyst Ni0.5-Fe3O4 / BC obtained in Example 1 of this invention are shown, where a is the specific surface area diagram and b is the pore size distribution diagram. Figure 2 The images shown are TEM and HRTEM images of the catalyst Ni0.5-Fe3O4 / BC obtained in Example 1 of this invention, where a is the TEM image, b is the HRTEM image, and c is the particle size distribution map. Figure 3 The images shown are TEM and SEM-Mapping images of the catalyst Ni0.5-Fe3O4 / BC obtained in Example 1 of this invention, where a is the SEM image and bf is the SEM-Mapping image. Figure 4The image shows the XRD pattern of the catalyst Ni0.5-Fe3O4 / BC obtained in Example 1 of this invention, with the dominant crystal plane {311} marked.
[0034] Figure 5 The images shown are electron microscope (TEM) images of the catalyst Ni0.5-Fe3O4 / USY obtained in Example 9 of this invention, where a is a TEM image and b is an HRTEM image.
[0035] Figure 6 The characterization of the catalyst Ni0.5-Fe3O4 / USY obtained in Example 9 of the present invention is shown, where a is XPS characterization and b is its valence state distribution. Detailed Implementation
[0036] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. The present invention will be further described below with reference to the embodiments.
[0037] Example 1 1. Preparation of biomass porous carbon carrier (BC) Clean and crush the coconut shells. Dry the crushed coconut shells in an oven at 110℃ until constant weight, and set aside. Weigh 10 g of the dried coconut shell fragments and mix them with 30 g of a 50% (w / w) phosphoric acid aqueous solution (prepared from 17.64 g of 85 wt% H3PO4 solution and 12.36 g of deionized water). Stir and impregnate at 80℃ for 4 hours. Transfer the impregnated mixture to a quartz boat and place it in a tube furnace for pyrolysis activation under a nitrogen atmosphere (flow rate 80 mL / min). The program is set to heat to 500℃ at a rate of 10℃ / min and hold at that temperature for 2 hours. Then, allow it to cool naturally to room temperature under a nitrogen atmosphere. Wash the cooled pyrolysis product repeatedly with hot water at 80℃ until the washing solution is neutral (pH=7). Dry the washed solid product in an oven at 110℃. Place the dried solid in a covered crucible and place it in a muffle furnace for heat treatment at 350℃ for 0.5 hours under an air atmosphere. The heat-treated product was mixed with 20 mL of concentrated sulfuric acid and sulfonated by stirring in an oil bath at 150°C for 2 hours. After the reaction, the mixture was cooled and repeatedly washed with deionized water until neutral. The final product was placed in a vacuum drying oven and dried under vacuum at 100°C for 12 hours to obtain the biomass porous carbon material, denoted as BC. Figure 1 As shown in a and b, the specific surface area of the BC material is 850 m² / g, and the pore size is approximately 7 nm.
[0038] 2. In-situ synthesis of Fe3O4 nanoparticles and Ni loading Weigh 1.62 g FeCl3·6H2O, 0.8 g sodium citrate, and 0.5 g polyvinylpyrrolidone (PVP) and dissolve them together in 40 mL of deionized water. Add 2.67 g of the BC support prepared in step 1 and stir until homogeneous. Under vigorous stirring, add sodium hydroxide solution dropwise to precisely adjust the pH of the mixture to 12.5. Transfer the pH-adjusted mixture to a 100 mL stainless steel hydrothermal reactor lined with polytetrafluoroethylene and react at 160 °C for 12 hours. After the reaction, allow it to cool naturally to room temperature. Filter the hydrothermal product and wash it several times with deionized water and anhydrous ethanol to remove impurities. Dry the washed solid under vacuum at 80 °C overnight to obtain an intermediate loaded with Fe3O4 nanoparticles, denoted as Fe3O4@BC. Weigh 1.0 g of the above Fe3O4@BC intermediate and disperse it in 10 mL of deionized water. Based on a Ni to Fe3O4 molar ratio of 0.5:1, the corresponding mass of nickel nitrate (Ni(NO3)2·6H2O) was calculated and weighed, and added to the above suspension. The mixture was stirred and impregnated at room temperature for 12 hours. The impregnated mixture was filtered, and the resulting solid was dried at 80℃. The dried solid was placed in a porcelain boat and calcined in a muffle furnace at 400℃ for 3 hours under an air atmosphere. The calcined sample was transferred to a tube furnace and reduced at 450℃ for 2 hours under a 10% H2 / N2 mixed gas atmosphere (flow rate 100 mL / min). After the sample cooled to room temperature under a protective atmosphere, it was removed, yielding the target catalyst, denoted as Ni0.5-Fe3O4 / BC. Figure 2 As shown in Figures a~c, the composite nanoparticles have a particle size of approximately 10 nm. Figure 3 As shown in Figures a to f, the active components Ni and Fe species are uniformly distributed on the surface of the support. Figure 4 The active phase Fe3O4 crystal plane shown is dominated by {311}.
[0039] 3. Catalyst performance evaluation 1 g of polypropylene powder was weighed and placed in a reactor. Then, 0.1 g of catalyst and 10 g of deionized water as a hydrogen source were added to the reactor. The air in the device was replaced with N2 and N2 was introduced into the reactor. Then, 3 MPa CO was introduced into the reactor and the heating device was used to carry out the reaction. The reaction temperature was 330℃ and the reaction time was 300 min. After the reaction was completed, the resulting solution was characterized and calculated. The conversion rate and selectivity are listed in Table 1.
[0040] Example 2 This embodiment aims to illustrate that by preparing Fe3O4 nanoparticles using a conventional co-precipitation method and loading metallic Ni using an impregnation-mixing method, a catalyst with the bifunctional activity described in this invention can also be prepared, proving the effectiveness of the basic structure of "Fe3O4 and metallic M supported on a porous support".
[0041] Accurately weigh FeCl2·4H2O (corresponding to Fe 2+ ) and FeCl3·6H2O (corresponding to Fe 3+ ), according to Fe 2+ :Fe 3+ The two molecules were dissolved in 80 mL of deionized water (bubbled under nitrogen) at a molar ratio of 1:2. The solution was transferred to a three-necked flask and heated to 80 °C under nitrogen protection with continuous mechanical stirring. While maintaining the temperature at 80 °C and vigorous stirring, a 25% (w / w) ammonia solution was rapidly added dropwise using a constant-pressure dropping funnel until the pH of the mixed solution stabilized at 10.0. During the addition, ultrasonic oscillation (100 W) was used throughout to promote uniform nucleation and dispersion and inhibit particle aggregation. After the addition was complete, the mixture was stirred and matured at 80 °C under nitrogen protection for 1 hour. After the reaction was complete, the resulting black magnetic precipitate was separated using an external magnet, and the supernatant was discarded. The precipitate was repeatedly washed with hot deionized water at 60 °C until the conductivity of the washing solution remained constant and it was neutral (pH≈7). The washed precipitate was transferred to a vacuum drying oven and dried at 60 °C for 12 hours to obtain Fe3O4-CP powder.
[0042] Weigh 1.0 g of the biomass porous carbon support (BC) prepared according to the method of Example 1, disperse it in 10 mL of deionized water, and sonicate it for 10 minutes to ensure thorough dispersion. Accurately weigh 0.03 g of Fe3O4-CP powder prepared in this example (this mass is equivalent to the theoretical loading of Fe element in Example 1) and add it to the above BC suspension. Sonicate it at room temperature for 30 minutes, then mechanically stir it for 12 hours to allow the Fe3O4-CP particles to initially combine with the BC support, obtaining mixed slurry A. Based on the molar ratio of Ni to Fe3O4 of 0.5:1, calculate and weigh the corresponding mass of nickel nitrate (Ni(NO3)2·6H2O), dissolve it in 2 mL of deionized water to prepare a solution. Add this solution dropwise to mixed slurry A, and continue stirring and impregnation at room temperature for 12 hours. The subsequent heat treatment steps are consistent with those in Example 1: filter the impregnated mixture, and dry the resulting solid at 80°C for 6 hours. The dried solid was placed in a porcelain boat and calcined in a muffle furnace under static air atmosphere at a rate of 2 °C / min to 400 °C for 3 hours. Then, the calcined sample was transferred to a tube furnace and calcined in a 10% H₂ / N₂ mixed gas atmosphere at a rate of 5 °C / min to 450 °C for 2 hours. After cooling to room temperature under nitrogen atmosphere, the sample was removed to obtain the catalyst, denoted as Ni₀.₅-Fe₃O₄(CP) / BC.
[0043] 1 g of polypropylene powder was weighed and placed in a reactor. Then, 0.1 g of catalyst and 10 g of deionized water as a hydrogen source were added to the reactor. The air in the device was replaced with N2 and N2 was introduced into the reactor. Then, 3 MPa CO was introduced into the reactor and the heating device was used to carry out the reaction. The reaction temperature was 330℃ and the reaction time was 300 min. After the reaction was completed, the resulting solution was characterized and calculated. The conversion rate and selectivity are listed in Table 1.
[0044] Example 3 The difference from Example 1 is as follows: Ni(NO3)2·6H2O was added to the solution at a Ni / Fe3O4 molar ratio of 1:1, and the mixture was stirred at room temperature for 12 h. The stirred liquid was then filtered and transferred to a ceramic boat, calcined in air for 3 h, and then transferred to a tube furnace for reduction at 450 °C for 2 h in a 10% H2 / N2 atmosphere with a flow rate of 100 mL / min to obtain the Ni-Fe3O4 / BC catalyst.
[0045] 1 g of polypropylene powder was weighed and placed in a reactor. Then, 0.1 g of catalyst and 10 g of deionized water as a hydrogen source were added to the reactor. The air in the device was replaced with N2 and N2 was introduced into the reactor. Then, 3 MPa CO was introduced into the reactor and the heating device was used to carry out the reaction. The reaction temperature was 330℃ and the reaction time was 300 min. After the reaction was completed, the resulting solution was characterized and calculated. The conversion rate and selectivity are listed in Table 1.
[0046] Example 4 The difference from Example 1 is that Ni(NO3)2·6H2O was added to the solution at a Ni / Fe3O4 molar ratio of 0.75:1, and the mixture was stirred for 12 h at room temperature. The stirred liquid was then filtered and transferred to a ceramic boat, calcined in air for 3 h, and then transferred to a tube furnace for reduction at 450 °C for 2 h in a 10% H2 / N2 atmosphere with a flow rate of 100 mL / min to obtain the Ni0.75-Fe3O4 / BC catalyst.
[0047] 1 g of polypropylene powder was weighed and placed in a reactor. Then, 0.1 g of catalyst and 10 g of deionized water as a hydrogen source were added to the reactor. The air in the device was replaced with N2 and N2 was introduced into the reactor. Then, 3 MPa CO was introduced into the reactor and the heating device was used to carry out the reaction. The reaction temperature was 330℃ and the reaction time was 300 min. After the reaction was completed, the resulting solution was characterized and calculated. The conversion rate and selectivity are listed in Table 1.
[0048] Example 5 The difference from Example 1 is that Ni(NO3)2·6H2O was added to the solution at a Ni / Fe3O4 molar ratio of 0.25:1, and the mixture was stirred for 12 h at room temperature. The stirred liquid was then filtered and transferred to a ceramic boat, calcined in air for 3 h, and then transferred to a tube furnace for reduction at 450 °C for 2 h in a 10% H2 / N2 atmosphere with a flow rate of 100 mL / min to obtain the Ni0.25-Fe3O4 / BC catalyst.
[0049] 1 g of polypropylene powder was weighed and placed in a reactor. Then, 0.1 g of catalyst and 10 g of deionized water as a hydrogen source were added to the reactor. The air in the device was replaced with N2 and N2 was introduced into the reactor. Then, 3 MPa CO was introduced into the reactor and the heating device was used to carry out the reaction. The reaction temperature was 330℃ and the reaction time was 300 min. After the reaction was completed, the resulting solution was characterized and calculated. The conversion rate and selectivity are listed in Table 1.
[0050] Example 6 The difference from Example 1 is that the addition of Ni(NO3)2·6H2O to the catalyst precursor was omitted, thus obtaining the Fe3O4 / BC catalyst.
[0051] 1 g of polypropylene powder was weighed and placed in a reactor. Then, 0.1 g of catalyst and 10 g of deionized water as a hydrogen source were added to the reactor. The air in the device was replaced with N2 and N2 was introduced into the reactor. Then, 3 MPa CO was introduced into the reactor and the heating device was used to carry out the reaction. The reaction temperature was 330℃ and the reaction time was 300 min. After the reaction was completed, the resulting solution was characterized and calculated. The conversion rate and selectivity are listed in Table 1.
[0052] Example 7 The difference from Example 1 is as follows: Pt(NH3)4(NO3)2 tetraammine nitrate was added to the solution at a Pt / Fe3O4 molar ratio of 0.5:1, and the mixture was stirred for 12 h at room temperature. The stirred liquid was then filtered and transferred to a ceramic boat, calcined in air for 3 h, and then transferred to a tube furnace for reduction at 450 °C for 2 h under a 10% H2 / N2 atmosphere with a flow rate of 100 mL / min to obtain the Pt0.5-Fe3O4 / BC catalyst.
[0053] 1 g of polypropylene powder was weighed and placed in a reactor. Then, 0.1 g of catalyst and 10 g of deionized water as a hydrogen source were added to the reactor. The air in the device was replaced with N2 and N2 was introduced into the reactor. Then, 3 MPa CO was introduced into the reactor and the heating device was used to carry out the reaction. The reaction temperature was 330℃ and the reaction time was 300 min. After the reaction was completed, the resulting solution was characterized and calculated. The conversion rate and selectivity are listed in Table 1.
[0054] Example 8 The difference from Example 1 is that (NH4)6Mo7O was added to the solution at a Mo / Fe3O4 molar ratio of 0.5:1. 24 ·4H2O, continue stirring at room temperature for 12 h; filter the stirred liquid and transfer it to a ceramic boat, calcine in air atmosphere for 3 h, after which transfer it to a tube furnace for reduction, 10% H2 / N2 atmosphere, flow rate 100 mL / min, 450℃ for 2 h to obtain Mo0.5-Fe3O4 / BC catalyst.
[0055] 1 g of polypropylene powder was weighed and placed in a reactor. Then, 0.1 g of catalyst and 10 g of deionized water as a hydrogen source were added to the reactor. The air in the device was replaced with N2 and N2 was introduced into the reactor. Then, 3 MPa CO was introduced into the reactor and the heating device was used to carry out the reaction. The reaction temperature was 330℃ and the reaction time was 300 min. After the reaction was completed, the resulting solution was characterized and calculated. The conversion rate and selectivity are listed in Table 1.
[0056] Example 9 The difference from Example 1 is as follows: 1 g of USY molecular sieve and 10 mL of deionized water were added sequentially to a 20 mL beaker. 0.03 g of Fe3O4 black powder was then mixed with the water and stirred until homogeneous. NiNO3 was added to the solution at a Ni / Fe3O4 molar ratio of 0.5:1, and stirring was continued at room temperature for 12 h. The stirred liquid was then filtered and transferred to a ceramic boat, calcined in air for 3 h, and then transferred to a tube furnace for reduction at 450 °C for 2 h under a 10% H2 / N2 atmosphere at a flow rate of 100 mL / min, to obtain the Ni0.5-Fe3O4 / USY catalyst. Figure 5 As shown, by Figure 5 As can be seen from a, the Ni0.5-Fe3O4 / USY catalyst has a complete structure, indicating that the active phase loading process did not cause structural damage to the support. Figure 5 As can be seen in b, the active phase components are uniformly supported on the support surface. The catalyst was characterized as follows: Figure 6 XPS characterization results of Ni show that, compared with Fe3O4 / USY, the introduction of Ni has a stronger promoting effect on the electronic structure transformation of Fe3O4. Figure 6 As can be seen from b, the introduction of Ni greatly increases the proportion of divalent iron in the reduction of iron oxide to Fe3O4, thereby promoting the in-situ generation of hydrogen in the subsequent reaction.
[0057] 1 g of polypropylene powder was weighed and placed in a reactor. Then, 0.1 g of catalyst and 10 g of deionized water as a hydrogen source were added to the reactor. The air in the device was replaced with N2 and N2 was introduced into the reactor. Then, 3 MPa CO was introduced into the reactor and the heating device was used to carry out the reaction. The reaction temperature was 330℃ and the reaction time was 300 min. After the reaction was completed, the resulting solution was characterized and calculated. The conversion rate and selectivity are listed in Table 1.
[0058] Example 10 The difference from Example 1 is as follows: 1 g of polypropylene powder was weighed and placed in a reactor, and then 0.1 g of catalyst and 10 g of deionized water as a hydrogen source were added to the reactor. The air in the device was replaced with N2 and N2 was introduced into the reactor. Then, 3 MPa CO was introduced into the reactor and the reaction was carried out by the heating device. The reaction temperature was 310°C and the reaction time was 300 min. After the reaction was completed, the resulting solution was characterized and calculated. The conversion rate and selectivity are listed in Table 1.
[0059] Example 11 The difference from Example 1 is as follows: 1 g of polypropylene powder was weighed and placed in a reactor, and then 0.1 g of catalyst and 10 g of deionized water as a hydrogen source were added to the reactor. The air in the device was replaced with N2 and N2 was introduced into the reactor. Then, 3 MPa CO was introduced into the reactor and the reaction was carried out by the heating device. The reaction temperature was 350°C and the reaction time was 300 min. After the reaction was completed, the resulting solution was characterized and calculated. The conversion rate and selectivity are listed in Table 1.
[0060] Example 12 The difference from Example 1 is as follows: 1 g of polypropylene powder was weighed and placed in a reactor, and then 1 g of catalyst and 10 g of deionized water as a hydrogen source were added to the reactor. The air in the device was replaced with N2 and N2 was introduced into the reactor. Then, 3 MPa CO was introduced into the reactor and the heating device was used to carry out the reaction. The reaction temperature was 330°C and the reaction time was 300 min. After the reaction was completed, the resulting solution was characterized and calculated. The conversion rate and selectivity are listed in Table 1.
[0061] Example 13 The difference from Example 1 is as follows: 1 g of polypropylene powder was weighed and placed in a reactor, and then 0.01 g of catalyst and 10 g of deionized water as a hydrogen source were added to the reactor. The air in the device was replaced with N2 and N2 was introduced into the reactor. Then, 3 MPa CO was introduced into the reactor and the reaction was carried out by the heating device. The reaction temperature was 330°C and the reaction time was 300 min. After the reaction was completed, the resulting solution was characterized and calculated. The conversion rate and selectivity are listed in Table 1.
[0062] Example 14 The difference from Example 1 is as follows: 1 g of polypropylene powder was weighed and placed in a reactor, and then 0.1 g of catalyst and 10 g of deionized water as a hydrogen source were added to the reactor. The air in the device was replaced with N2 and N2 was introduced into the reactor. Then, 3 MPa CO was introduced into the reactor and the reaction was carried out by the heating device. The reaction temperature was 330°C and the reaction time was 200 min. After the reaction was completed, the resulting solution was characterized and calculated. The conversion rate and selectivity are listed in Table 1.
[0063] Example 15 The difference from Example 1 is as follows: 1 g of polypropylene powder was weighed and placed in a reactor, and then 0.1 g of catalyst and 10 g of deionized water as a hydrogen source were added to the reactor. The air in the device was replaced with N2 and N2 was introduced into the reactor. Then, 3 MPa CO was introduced into the reactor and the reaction was carried out by the heating device. The reaction temperature was 330°C and the reaction time was 400 min. After the reaction was completed, the resulting solution was characterized and calculated. The conversion rate and selectivity are listed in Table 1.
[0064] Example 16 The difference from Example 1 is as follows: 1 g of polypropylene powder was weighed and placed in a reactor, and then 0.1 g of catalyst and 10 g of deionized water as a hydrogen source were added to the reactor. The air in the device was replaced with N2 and N2 was introduced into the reactor. Then, 2 MPa CO was introduced into the reactor and the reaction was carried out by the heating device. The reaction temperature was 330°C and the reaction time was 300 min. After the reaction was completed, the resulting solution was characterized and calculated. The conversion rate and selectivity are listed in Table 1.
[0065] Detection method: GC-MS results were obtained and analyzed using a Shimadzu QP2010 Plus gas chromatograph-mass spectrometer. An HP 190915-433 capillary column was used for the assay. The initial temperature was set to 80℃ and held for two minutes, followed by a temperature increase of 5℃·min. -1 The temperature was increased to 260℃ at a rate of 10℃·min. -1 The temperature was rapidly increased to 280°C. The injection port temperature was set to 300°C. High-purity helium was used as the carrier gas at a flow rate of 2.4 mL / min. -1 The split ratio was set to 5.0:1, the injection volume to 0.2 μL, and the solvent delay time to 3 minutes. The ion source was set to electron impact (EI) mode, with an electron impact energy of 70 eV and a mass-charge ratio measurement range of 30–500. The obtained substances were classified according to carbon number, and the C5–C22 fraction was selected as the liquid fuel. The conversion and selectivity were calculated using the following formulas:
[0066] in, This represents the molar amount of unreacted polypropylene. This represents the initial molar amount of polypropylene. This represents the molar amount of each polypropylene product.
[0067] Table 1. Results of polypropylene conversion and liquid fuel selectivity in each example.
[0068] The number of the two acid types measured by pyridine infrared spectroscopy is shown in Table 2.
[0069] Table 2. Acidity of Ni0.5-Fe3O4 / BC catalyst at different temperatures
[0070] As shown in Tables 1 and 2, the Ni0.5-Fe3O4 / BC catalyst exhibited the highest activity in the catalytic degradation reaction of waste plastics. Biomass activated carbon efficiently supported tunable Brønsted (B) and Lewis (L) acid sites, and its unique microporous channels served as the core of the catalytic degradation process, effectively breaking the C-C bonds of the plastic polymer to generate smaller hydrocarbon fragments. Ni controlled the product distribution; by controlling the degree of hydrogenation, the ratio of olefins to BTX (benzene, toluene, xylene) in the products could be influenced. Moderate hydrogenolysis could directionally break the C-C bonds, generating the target small-molecule olefins. Fe3O4 efficiently converted CO and H2O into active H2 and CO2, providing a continuous hydrogen source for the entire hydrogenation / hydrogenolysis process. The generated CO2 also participated in the reaction as a weak oxidant to some extent, helping to remove surface carbon and significantly improving the cyclic performance of the catalyst. The Ni0.5-Fe3O4(CP) / BC obtained in Example 2 also showed near-complete conversion of PP, demonstrating that the catalyst generated by the crystal facet orientation induction of Fe3O4 has the same activity. However, the liquid fuel selectivity was lower than that of Ni0.5-Fe3O4 / BC, indicating that the special crystal facet, i.e., the {311} exposed Fe3O4, is beneficial to the formation of liquid fuels in the process of catalyzing the in-situ hydrogen degradation of polypropylene from carbon monoxide. Furthermore, the optimal Ni to Fe3O4 loading ratio was obtained through Examples 3-6. Considering both polypropylene conversion and selectivity, Examples 7 and 8 demonstrated that Ni exhibited the best catalytic performance in this coupled reaction. Example 9 demonstrated that the Ni and Fe3O4 active phase supported on the molecular sieve support could also catalyze the degradation of polypropylene to liquid fuels in this reaction. Examples 10-16 confirmed the optimal catalytic conditions for Ni0.5-Fe3O4 / BC, namely 330°C, 3 MPa CO, and a reaction time of 300 min.
[0071] Application Example 1 The Ni0.5-Fe3O4 / BC prepared in Example 1 was used in a catalytic waste plastic degradation and recycling experiment.
[0072] 1 g of polypropylene powder was weighed and placed in a reactor. Then, 0.1 g of Ni0.5-Fe3O4 / BC catalyst and 4 g of deionized water as a hydrogen source were added to the reactor. The air in the reactor was replaced with N2, and then CO at 3 MPa was introduced into the reactor. The reaction was carried out by heating the reactor at 330℃ for 300 min. After the reaction was completed, the resulting solution was characterized and the conversion rate and selectivity are listed in Table 3. The catalyst was used to conduct the reaction 5 times to evaluate the recycling capacity of the catalyst in Example 1.
[0073] Under the same reaction conditions, the conversion rate and selectivity of the waste plastic degradation catalyst prepared in Example 1 for catalytic polypropylene degradation cycle experiment are shown in Table 3.
[0074] Table 3. Cyclic Experiment of PP Degradation Catalyst Prepared in Example 1
[0075] Application Example 1 illustrates that the Ni0.5-Fe3O4 / BC catalyst prepared in this invention exhibits extremely high catalytic activity and structural stability. It can achieve complete degradation of PP powder at 330℃, and its selectivity for efficient conversion to liquid fuel is well maintained. Due to the weak reducing properties of the surface Fe3O4 nanoparticles, a reverse Boudouard reaction (C + CO2 → 2CO) may occur on the catalyst surface, slightly vaporizing some of the carbon deposits and maintaining the catalyst's cycle stability.
[0076] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a bifunctional catalyst for coupling water-gas shift and plastic hydrogenolysis reactions, characterized in that, Includes the following steps: S1. Support preparation: Prepare or provide a porous support; S2. In-situ synthesis and loading of Fe3O4 nanoparticles: Fe3O4 nanoparticles with exposed {311} crystal planes were grown in situ on the support using a hydrothermal method synergistically controlled by polymer and surfactant to obtain Fe3O4@support precursor; S3. Loading of co-catalytic metal M: The salt solution containing co-catalytic metal M is loaded onto the Fe3O4@support precursor obtained in step S2 by impregnation method; S4. Activation treatment: The loaded material is heat-treated in a reducing atmosphere to obtain the bifunctional catalyst; In step S2, the hydrothermal method specifically involves dissolving iron salt, surfactant, and polymer in water, adding a carrier, adjusting the pH to 12-13, then transferring the mixture to a hydrothermal reactor and reacting it at 150-180°C for 10-14 hours. After the reaction is complete, the mixture is washed and dried to obtain the Fe3O4@carrier precursor. In step S2, the polymer is selected from one or more of polyvinylpyrrolidone, polyvinyl alcohol, and polyethylene glycol; The surfactant is selected from one or more of citrate, tartrate, oxalate, and EDTA; The porous carrier is selected from one or more composite materials selected from biomass-derived porous carbon, Y-type molecular sieve, Beta molecular sieve, ZSM-5 molecular sieve, alumina, silicon oxide, zinc oxide, silicon carbide, and molybdenum carbide. The co-catalytic metal M is selected from at least one of the transition metals Co, Ni, Mo, and W, or the noble metals Ru, Pd, and Pt.
2. The method for preparing the bifunctional catalyst for coupling water-gas shift and plastic hydrogenolysis reaction according to claim 1, characterized in that, In step S4, the activation treatment includes two heat treatments: first, calcination at 300-500°C for 1-5 hours in an oxygen-containing atmosphere; then, reduction at 350-500°C for 1-4 hours in a reducing atmosphere.
3. A bifunctional catalyst obtained by the preparation method according to claim 1, characterized in that, The bifunctional catalyst comprises a composite active component supported on a porous carrier, the composite active component comprising Fe3O4 nanoparticles with exposed crystal faces {311}, and a co-catalytic metal M.
4. The bifunctional catalyst according to claim 3, characterized in that, The Fe3O4 nanoparticles form an M-Fe3O4 composite active phase that interacts closely with the co-catalytic metal M; the molar ratio of the co-catalytic metal M to Fe3O4 is 0.25-1:
1.
5. The bifunctional catalyst according to claim 3, characterized in that, The carrier is biomass-derived porous carbon with a specific surface area of 500-1000 m². 2 / g, with a pore size of 5-15 nm.
6. The bifunctional catalyst according to claim 3, characterized in that, The Fe3O4 nanoparticles form an M-Fe3O4 composite active phase that interacts closely with the co-catalytic metal M, and the nanoparticles loaded on the support have a particle size of 5-50 nm.
7. The application of the bifunctional catalyst according to claim 3 in the resource utilization of waste plastics, characterized in that, The specific method of the application is as follows: waste plastic, water, the bifunctional catalyst of claim 3, and carbon monoxide are placed together in a reactor for reaction; the bifunctional catalyst simultaneously catalyzes the water-gas shift reaction to generate active hydrogen, and uses the active hydrogen to catalyze the hydrogenolysis reaction of plastic to convert it into liquid fuel.
Citation Information
Patent Citations
Remediation method of hexavalent chromium contaminated soil
CN116731718A